Carbonic anhydrase III (Car3) is not required for fatty acid synthesis and does not protect against high-fat diet induced obesity in mice ... - Renner, SW; Walker, LM; Forsberg, LJ; Sexton, JZ; Brenman, JE (Public Library of Science (PLoS), 2017)
Carbonic anhydrases are a family of enzymes that catalyze the reversible condensation of water and carbon dioxide to carbonic acid, which spontaneously dissociates to bicarbonate. Carbonic anhydrase III (Car3) is nutritionally regulated at both the mRNA and protein level. It is highly enriched in tissues that synthesize and/or store fat: liver, white adipose tissue, brown adipose tissue, and skeletal muscle. Previous characterization of Car3 knockout mice focused on mice fed standard diets, not high-fat diets that significantly alter the tissues that highly express Car3. We observed lower protein levels of Car3 in high-fat diet fed mice treated with niclosamide, a drug published to improve fatty liver symptoms in mice. However, it is unknown if Car3 is simply a biomarker reflecting lipid accumulation or whether it has a functional role in regulating lipid metabolism. We focused our in vitro studies toward metabolic pathways that require bicarbonate. To further determine the role of Car3 in metabolism, we ...